Numerical multiscale homogenization approach for linearly viscoelastic 3D interlock woven composites. (15th May 2019) - Courtois, A.; Marcin, L.; Benavente, M.; Ruiz, E.; Lévesque, M.
Abstract: This work aims at modeling the homogenized behavior of a polymer matrix composite reinforced with three dimensional (3D) woven fabric. The effective warp and weft tows' properties were determined by numerical homogenization with Abaqus considering elastic fibers, a viscoelastic matrix and periodic boundary conditions. The temperature- and cure-dependent linearly viscoelastic model previously developed by the authors for this particular polymer matrix was implemented into a subroutine using a differential strategy. A second homogenization procedure was carried out to obtain the mesoscopic structure homogenized behavior. Moreover, rectangular composite plates were manufactured by Resin Transfer Molding (RTM) and isothermal creep tests were carried out to study the material's viscoelastic behavior at high temperatures below the resin's glass transition temperature. Experimental results were compared to the temperature-dependent homogenized linearly viscoelastic model predictions. This model is a step forward for the accurate prediction of the residual stresses developed during the manufacturing of structural parts made out of 3D woven interlock composites.